DNA polymerase [gamma] and disease: what we have learned from yeast - Lodi, Tiziana; Dallabona, Cristina; Nolli, Cecilia; Goffrini, Paola; Donnini, Claudia; Baruffini, Enrico (Frontiers in Genetics, 2015)
Mip1 is the Saccharomyces cerevisiae DNA polymerase [gamma] (Pol [gamma]), which is responsible for the replication of mitochondrial DNA (mtDNA). It belongs to the family A of the DNA polymerases and it is orthologous to human POLGA. In humans, mutations in POLG(1) cause many mitochondrial pathologies, such as PEO, Alpers’ syndrome and ataxia-neuropathy syndrome, all of which present instability of mtDNA, which results in impaired mitochondrial function in several tissues with variable degrees of severity. In this review, we summarize the genetic and biochemical knowledge published on yeast mitochondrial DNA polymerase from 1989, when the MIP1 gene was first cloned, up until now. The role of yeast is particularly emphasized in i) validating the pathological mutations found in human POLG and modeled in MIP1, ii) determining the molecular defects caused by these mutations and iii) finding the correlation between mutations/polymorphisms in POLGA and mtDNA toxicity induced by specific drugs. We also describe recent findings regarding the discovery of molecules able to rescue the phenotypic defects caused by pathological mutations in Mip1, and the construction of a model system in which the human Pol [gamma] holoenzyme is expressed in yeast and complements the loss of Mip1.